Under the Tourist Gaze: Kathmandu in Popular Culture - Dahal, Arvind (JODEM: Journal of Language and Literature, 2020)
This research explores the shifts and continuities of representing Kathmandu City in Western cinematic and musical creations since 1970s. My research concerns with the representations of Kathmandu in the popular culture intends to explore the imagination of Kathmandu as a touristic place and how they represent the city and produce images in the popular culture which expands far beyond the visual apprehension and enjoyment of a landscape. While doing so my research first explores the representations, practices and processes of identity formation and cultural negotiations that are brought about in the city by tourism and secondly, it analyses the content and the visual representations of the movies and songs relying primarily on the theoretical tools of Popular Culture and secondarily the image production of the landscape in terms of Tourist gaze.